Ocular trauma: prevention - Pradhan, Eli (Nepalese Journal of Ophthalmology, 2017)
Ocular trauma is an important cause of unilateral visual impairment worldwide. According to Nepal blindness survey (Brillinat et al, 1985), it accounted for 2.4% of blindness, and in another community based study (Upadhyay M et al, 2001), the prevalence of ocular trauma was observed to be 0.7%. The Bhaktapur Eye Study confirms that “corneal trauma leading to ulceration” is the second most common cause of blindness after cataract in Nepal.